Residues of Organochlorine Pesticides in Human Blood in Ahmedabad, India - Bhatnagar, V.K.; Kashyap, Rekha; Saiyed, H.N. (Asian Journal of Chemistry, 2010)
Three studies on the estimation of residues of organochlorine pesticides in the general population of Ahmedabad at different intervals were carried out. Observed trend for these contaminants is descending which may be due to restrictions imposed on the use of these chemicals. However, these levels are still higher than the studies originating from other developing countries.